Thermoelectric performance of Nb-doped SrTiO3 enhanced by reduced graphene oxide and Sr deficiency cooperation. (March 2019) - Okhay, Olena; Zlotnik, Sebastian; Xie, Wenjie; Orlinski, Krzysztof; Hortiguela Gallo, Maria J.; Otero-Irurueta, Gonzalo; Fernandes, Antonio J.S.; Pawlak, Dorota A.; Weidenkaff, Anke; Tkach, Alexander
Abstract: Oxide materials are of current interest as high-temperature thermoelectrics in the automotive and manufacturing energy-harvesting sectors due to high chemical robustness, low toxicity and low cost. Driven by a need to improve the thermoelectric performance of n-type oxides to the level of p-type analogues, ceramics and composites based on donor-doped SrTiO3 are considered as a promising material. Here Nb-doped SrTiO3 with Nb content of 10 and 15% as well as Sr/(Nb + Ti) ratio of 1.00 and 0.98 was mixed with 0.6 wt. % of graphene oxide (GO) prepared by Hummer-based method and conventionally sintered in atmosphere of H2 /N2 to reduce both Nb-doped SrTiO3 and GO. Addition of reduced GO in combination with introduction of Sr vacancies provides a synergistic effect of fastening charge transport and thereby increasing electrical conductivity σ and suppressing the thermal conductivity κ . These factors, together with a moderate Seebeck coefficient S, result in a high power factor PF  = S 2  ×  σ up to ∼1.98 mW/(K 2 m) and thermoelectric figure of merit ZT  =  PF  ×  T / κ up to 0.29. These findings offer further prospects for seeking high performance SrTiO3 -based thermoelectrics by modification with reduced GO. Graphical abstract: